110 Post-injury ptsd and depression in seriously injured urban black men. (19th September 2017) - Richmond, Therese; Shults, Justine; Webster, Jessica; Robinson, Andrew; Wiebe, Douglas; Reilly, Patrick; Kassam-Adams, Nancy
Abstract : Purpose: To describe the burden of post-injury PTSD and depression and the contribution of injury and acute stress responses to PTSD and depression severity 3 months post-discharge. Methods/Approach: 607 seriously injured Black men were enrolled during hospitalisation for injury. 474 have completed follow-up 3 months post-discharge at the time of analysis. Demographics, injury characteristics (mechanism, injury severity), and acute stress responses: Trauma Screening Questionnaire (TSQ), Peri-traumatic Distress Inventory (PDI), Rand Peri-traumatic Dissociation Questionnaire (Rand), were collected in hospital. PTSD (PCL-5) and Depression (QIDSsr16) were collected 3 months post-discharge in the participant's home, with higher scores reflecting more severe symptoms. Linear regression was used to identify characteristics associated with PTSD and depression symptom severity. Results: Mean age 36.8 years (SD15.6). Mean Injury Severity 9.2 (SD7.5). 53% violent and 47% unintentional injury. 137 (28.8%) had PTSD and 169 (35.7%) had depression at 3 months. Significant correlates (p<0.05) of PTSD were PDI (Î²=0.154), TSQ (Î²=0.281), violent mechanism of injury (Î²=0.138), and age (Î²=0.021), accounting for 29% of the variance in PTSD symptom severity. Significant correlates (p<0.05) of depression were PDI (Î²=0.177), TSQ (Î²=0.272) and injury severity (Î²=0.021), accounting for 21% of variance in depression symptom severity. Conclusion: Injury characteristics and acute psychological stress responses contribute to PTSD and depression at 3 months after discharge with the acute stress responses accounting for the largest part of variance. Understanding early for psychological responses to injury can help to guide comprehensive care for those at highest risk for post-injury PTSD and depression. Significance/Contribution: Limited attention is paid to the psychological effects of the injury. For Black men who sustain serious injury, returning home from the hospital with unrecognised psychological consequences contributes to sub-optimal recovery. PTSD and depression may have behavioural manifestations that contribute to injury recidivism, self-medication for symptoms, or interactions with the criminal justice system.